Role of the Argentine Republic in the evolution of MERCOSUR - L. A. Kalinin (Ибероамериканские тетради)
The article presents an analysis of Argentina’s priorities in its integration policies within the Common Market of the South Cone (Mercosur) as well as the evolution of its approaches towards the relations with the block partners.